2019
DOI: 10.3390/polym11101639
|View full text |Cite
|
Sign up to set email alerts
|

Facile Strategy of Improving Interfacial Strength of Silicone Resin Composites Through Self-Polymerized Polydopamine Followed via the Sol-Gel Growing of Silica Nanoparticles onto Carbon Fiber

Abstract: In the present research, to enhance interfacial wettability and adhesion between carbon fibers (CFs) and matrix resin, hydrophilic silica nanoparticles (SiO2) were utilized to graft the surface of CFs. Polydopamine (PDA) as a “bio-glue” was architecturally built between SiO2 and CFs to obtain a strong adhesion strength and homogenous SiO2 distribution onto the surface of CFs. The facile modification strategy was designed by self-polymerization of dopamine followed by the hydrolysis of tetraethoxysilane (TEOS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Previously, we have successfully coated some inorganic fillers with polydopamine, which were further modified with secondary reaction because of the existing catechol groups of polydopamine [21,22]. Some recent reports also confirmed that polydopamine could be easily coated onto the surface of the nanoparticles [23][24][25].…”
Section: Introductionmentioning
confidence: 93%
“…Previously, we have successfully coated some inorganic fillers with polydopamine, which were further modified with secondary reaction because of the existing catechol groups of polydopamine [21,22]. Some recent reports also confirmed that polydopamine could be easily coated onto the surface of the nanoparticles [23][24][25].…”
Section: Introductionmentioning
confidence: 93%
“…Carbon-fiber-reinforced polymer composites have attracted scientific attention from many groups aiming for scientific research and industrial utilization, and are widely used as novel engineering materials in many fields because of their high tensile strength, light weight, and outstanding environmental stability [1][2][3][4][5][6]. Nevertheless, the practical application of carbon fiber (CF) composites has been limited because of the fibers' inert and smooth surfaces, as well as the poor quality of the resultant fiber-matrix interface [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Carbon ber reinforced polymer (CFRP) composites have a wide application in the elds of aerospace, automotive, and defense industries because of its excellent performance such as strong modulus, light weight, and environmental friendly [1][2][3]. However, ber surface is smooth and insu cient the active groups lead to a weak interface strength between CF and matrix, which limited wide-ranging application of the CFRP [4]. Previous investigations have attempted to avoid crack initiation and propagation in CFRP via improving the interfacial adhesion between CF and polymer [5,6].…”
Section: Introductionmentioning
confidence: 99%